Comment about the article: «Understanding of different front-of-package labels by the Spanish population: Results of a comparative study» - Grados-Jares, Manuel D. (2020)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.